Exome Sequencing Defines the Molecular Pathogenesis of Vein of Galen Malformation. (1st September 2019) - Kundishora, Adam; Zeng, Xue; Duran, Daniel; Allocco, August A; Choi, Jungmin; Jin, Sheng Chih; Conine, Sierra B; Nelson-Williams, Carol; Gaillard, Jonathan; Furey, Charuta G; Timberlake, Andrew T; Mansuri, Mohammad; et al.
Abstract: INTRODUCTION: Vein of Galen malformations (VOGMs) are morbid arteriovenous malformations, with poorly described genetis. 1 Despite improvement in endovascular treatment, VOGM mortality remains high. 2 VOGM has been reported as a rare finding in Capillary Malformation-Arteriovenous Malformation Syndrome (RASA1; OMIM #605384) and Hereditary Hemorrhagic Telangiectasia (ENG, ACVRL1; OMIM #187300, #600376). 3-4 Our previous work has identified EPH receptor tyrosine kinase as also playing a role in VOGM pathogenesis. 5 Here, we report a larger cohort of probands and identify a new gene in the same pathway as EPHB4 as playing a role in VOGM. METHODS: Germline DNA was isolated from 84 unrelated probands harboring radiographically confirmed VOGMs Both parents were available for 69/84 probands. Exome capture and paired-end WES was performed on DNA samples from participating individuals (n = 237). Data was bioinformatically analyzed to identify rare de-novo and transmitted mutations. Binomial analysis tested for exome-wide significance of mutational burden. RESULTS: Only 3/75 patients harbored mutations in previously reported VOGM-associated genes (2.3%; RASA1 n = 2, 1.1%; ACVRL1 n = 1). Significant enrichment of rare damaging mutations was found for a member of the EPH receptor tyrosine kinase family (EPHB4, n = 5; 6.0%; P  = 3.31 × 10–7, 36.62-fold enrichment). Entirely novel mutations in the integrin family were also identified (n = 2; 1.1%, P  = 6.03 × 10–5, 179.6-fold enrichment). Both of these mutations are located in the c-terminal domain and disrupt a binding motif. Furthermore, this integrin protein mutation is involved in the same pathway as EPHB4, although whether or not they directly interact remains unknown. CONCLUSION: This work represents an expansion upon the largest phenotyped, exome-sequenced VOGM cohort in the world. Having discovered a new gene in the same pathway as EPHB4 strongly implicates said pathway in VOMG development. We are currently pioneering tissue sampling from endovascular instruments used during treatment to explore potential somatic mutations. Our findings continue to uncover genetic determinants of VOGM pathogenesis, providing novel insight into vascular developmental biology.